Silver Nanoparticle-Modified Screen-Printed Carbon Electrodes for the Electrochemical Sensing of the Prostate-Specific Antigen - Makableh, Yahia F.; Athamneh, Tamara; Matar, Rama; Abu-Baker, Ahmad; Hijazi, Sara; Al-Qaisi, Aws (Engineering, Technology & Applied Science Research, 2026)
This study focuses on the development of an electrochemical aptamer-based biosensor based on silver Nanoparticle (AgNP)-modified Screen-Printed Carbon Electrodes (SPCEs) and its sensing potential against Prostate-Specific Antigen (PSA), a primary biomarker of Prostate Cancer (PCa). A significant challenge in conventional PCa screening methods is their inability to detect PSA with high sensitivity in early cancer stages. SPCEs modified with nanomaterials can overcome this limitation and revolutionize cancer diagnosis. The electrochemical behavior of the proposed biosensor was studied using voltametric and impedimetric methods. Atomic Force Microscopy (AFM) and Fourier Transform Infrared spectroscopy (FTIR) were also utilized to confirm the assembly of the sensor. The Limit of Detection (LOD) was assessed by deploying differential pulse voltammetry, where the sensor demonstrated high sensitivity and selectivity towards PSA. The LOD of the biosensor was 0.004 ng/ml, which underscores its potential as a robust tool for early PCa detection in point-of-care settings.